The influence of e-service quality on e-loyalty on Soco by Sociolla online retail customers in Indonesia - Cheryl Budiono; Prita Kusumawardhany (Southeast Asian Journal of Service Management, 2025)
This study aims to determine the influence between e-service quality, e-satisfaction, e-trust, and e-loyalty. The research object used in an online retail application SOCO by Sociolla in Indonesia. The data was processed using software named Smart PLS 3 with 190 primary data obtained through respondents and customers of SOCO by Sociolla in Indonesia. The results of this study indicate a supported relationships of efficiency on e-satisfaction and e-trust, privacy on e-satisfaction and e-trust, reliability on e-satisfaction and e-trust, emotional benefit on e-satisfaction, customer service on e-trust, e-trust on e-satisfaction, e-satisfaction on behavioural loyalty and attitudinal loyalty, e-trust on attitudinal loyalty, and then behavioural loyalty on attitudinal loyalty. In addition, there are non-supported relationships namely emotional benefit to e-trust, customer service to e-satisfaction, and then e-trust to behavioural loyalty.